Emotional Intelligence and Maternal Nutrition in Third Trimester Pregnancy for Anemia Prevention - Triharini, Mira; Armini, Ni Ketut Alit; Nastiti, Aria Aulia; Pradanie, Retnayu; Sa’diyah, Halimatus; Widya, Fadhilah Aliyyah (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2024)
Pregnant women in the third trimester require more nutrition to prevent anemia. Emotional intelligence (EI) helps manage emotions and make healthier dietary choices. This study aimed to determine the level of emotional intelligence among third-trimester pregnant women. A quantitative descriptive analytical design was used among 113 participants selected through purposive sampling. Data were collected using an emotional intelligence questionnaire developed by Daniel Goleman and a maternal nutrition assessment. Results indicated that self-awareness played a crucial role in food choices, as women with higher self-awareness were more likely to have adequate nutrition (55%). However, some pregnant women with inadequate nutrition also had high self-awareness (61,5%). Self-regulation showed no significant differences between groups, indicating challenges in maintaining a balanced diet. Motivation was high in both groups, but 69.2% women with inadequate nutrition still face barriers in applying motivation to healthy eating habits. Empathy and social skills were higher in the adequate nutrition group, suggesting the importance of social support. Healthcare workers can support better nutrition in mothers by strengthening their motivation, self-control, and awareness through counseling and group support.